Analysis of chronic myeloid leukaemia during deep molecular response by genomic PCR: a traffic light stratification model with impact on treatment-free remission - Machova Polakova, Katerina; Zizkova, Hana; Zuna, Jan; Motlova, Eliska; Hovorkova, Lenka; Gottschalk, Andrea; Glauche, Ingmar; Koblihova, Jitka; Pecherkova, Pavla; Klamova, Hana; Stastna Markova, Marketa; Srbova, Dana; et al. (Leukemia, 2020)
This work investigated patient-specific genomic BCR-ABL1 fusions as markers of measurable residual disease (MRD) in chronic myeloid leukaemia, with a focus on relevance to treatment-free remission (TFR) after achievement of deep molecular response (DMR) on tyrosine kinase inhibitor (TKI) therapy. DNA and mRNA BCR-ABL1 measurements by qPCR were compared in 2189 samples (129 patients) and by digital PCR in 1279 sample (62 patients). A high correlation was found at levels of disease above MR4, but there was a poor correlation for samples during DMR. A combination of DNA and RNA MRD measurements resulted in a better prediction of molecular relapse-free survival (MRFS) after TKI stop (n = 17) or scheduled interruption (n = 25). At 18 months after treatment cessation, patients with stopped or interrupted TKI therapy who were DNA negative/RNA negative during DMR maintenance (green group) had an MRFS of 80% and 100%, respectively, compared with those who were DNA positive/RNA negative (MRFS = 57% and 67%, respectively; yellow group) or DNA positive/RNA positive (MRFS = 20% for both cohorts; red group). Thus, we propose a "traffic light" stratification as a TFR predictor based on DNA and mRNA BCR-ABL1 measurements during DMR maintenance before TKI cessation.
Keywords: Neoplasm, Residual; Humans; messenger RNA; inhibitory proteinkinas; lidé středního věku; Female; Aged; dospělí; senioři; lidé; tyrosinkinasy; Withholding Treatment; nenasazení léčby; indukce remise; Adult; Protein Kinase Inhibitors; RNA, Messenger; ženské pohlaví; Male; Protein-Tyrosine Kinases; chronická myeloidní leukemie; Middle Aged; bcr-abl fúzní proteiny; Fusion Proteins, bcr-abl; polymerázová řetězová reakce; Remission Induction; Polymerase Chain Reaction; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; mužské pohlaví; reziduální nádor